Role of VAD Regimen as the First-Line Treatment in Multiple Myeloma - Mahmood, SS; Abedin, AKM; Islam, H; Jubaida, N; Kawsar, NM; Hoque, M (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i2.16357 JAFMC Vol.8(2) 2012 pp.64-69